How much territory can a single E. coli cell control? - El-Hajj, Ziad W.; Newman, Elaine B. (Frontiers in Microbiology, 2015)
Bacteria have been traditionally classified in terms of size and shape and are best known for their very small size. E. coli cells in particular are small rods, each 1-2 microns. However the size varies with the medium, and faster growing cells are larger because they must have more ribosomes to make more protoplasm per unit time, and ribosomes take up space. Indeed, Maaloe's experiments on how E. coli establishes its size began with shifts between rich and poor media. Recently much larger bacteria have been described, including Epulopiscium fishelsoni at 700 μm and Thiomargarita namibiensisis at 750 μm. These are not only much longer than E. coli cells but also much wider, necessitating considerable intracellular organization. Epulopiscium cells for instance, at 80 μm wide, enclose a large enough volume of cytoplasm to present it with major transport problems. This review surveys E. coli cells much longer than those which grow in nature and in usual lab cultures. These include cells mutated in a single gene (metK) which are 2-4x longer than their nonmutated parent. This metK mutant stops dividing when slowly starved of S-adenosylmethionine but continues to elongate to 50 μm and more. FtsZ mutants have been routinely isolated as long cells which form during growth at 42°C. The SOS response is a well-characterized regulatory network that is activated in response to DNA damage and also results in cell elongation. Our champion elongated E. coli is a metK strain with a further, as yet unidentified mutation, which reaches 750 μm with no internal divisions and no increase in width.